Desalination and Detoxification of Textile Wastewater by Novel Photocatalytic Electrolysis Membrane Reactor for Ecosafe Hydroponic Farming - Muhammed Iberia Aydin; Damla Ozaktac; Burak Yuzer; Mustafa Doğu; Hatice Inan; Hatice Eser Okten; Serdar Coskun; Huseyin Selcuk (Membranes, 2021)
In this study, a novel photoelectrocatalytic membrane (PECM) reactor was tested as an option for the desalination, disinfection, and detoxification of biologically treated textile wastewater (BTTWW), with the aim to reuse it in hydroponic farming. The anionic ion exchange (IEX) process was used before PECM treatment to remove toxic residual dyes. The toxicity evaluation for every effluent was carried out using the Vibrio fischeri, Microtox® test protocol. The disinfection effect of the PECM reactor was studied against E. coli. After PECM treatment, the 78.7% toxicity level of the BTTWW was reduced to 14.6%. However, photocatalytic desalination during treatment was found to be slow (2.5 mg L−1 min−1 at 1 V potential). The reactor demonstrated approximately 52% COD and 63% TOC removal efficiency. The effects of wastewater reuse on hydroponic production were comparatively investigated by following the growth of the lettuce plant. A detrimental effect was observed on the lettuce plant by the reuse of BTTWW, while no negative impact was reported using the PECM treated textile wastewater. In addition, all macro/micronutrient elements in the PECM treated textile wastewater were recovered by hydroponic farming, and the PECM treatment may be an eco-safe wastewater reuse method for crop irrigation.